Efektivitas Edukasi Digital dalam Meningkatkan Kesiapan dan Keselamatan Pasien Perioperatif: Literature Review - Tri Wahyuni Ismoyowati; Muhamad Arief Fadli; Sahat Tumpal Salomo; Henry Agus Agus (Journal of Innovative and Creativity (Joecy), 2026)
The perioperative period is a critical phase that requires optimal patient preparation to improve surgical outcomes and ensure patient safety. Inadequate patient knowledge regarding surgical procedures, anesthesia, postoperative care, and safety measures may increase anxiety, reduce adherence to perioperative instructions, and contribute to postoperative complications. Digital education has emerged as an innovative strategy to provide accessible, interactive, and patient-centered health education. This literature review aimed to analyze the effectiveness of digital educational interventions in improving perioperative patient preparedness and patient safety. A literature review was conducted using articles retrieved from PubMed, Scopus, ScienceDirect, ProQuest, and Google Scholar published between 2020 and 2025. The search employed keywords including "digital education", "perioperative education", "preoperative education", "patient safety", "multimedia education", "mobile health", and "surgical patient". Articles were selected based on predefined inclusion and exclusion criteria, and the quality of eligible studies was assessed before narrative synthesis. The reviewed studies consistently demonstrated that digital education delivered through videos, mobile applications, web-based platforms, virtual education, and multimedia programs significantly improved patients’ knowledge, reduced preoperative anxiety, enhanced adherence to perioperative instructions, increased satisfaction with healthcare services, and strengthened patient safety. Several studies also reported improvements in communication between healthcare professionals and patients, resulting in better perioperative outcomes. In conclusion, digital education is an effective and evidence-based strategy to improve perioperative preparedness and patient safety. Integrating digital educational media into perioperative nursing practice and multidisciplinary surgical care is recommended to optimize the quality of perioperative services